The The Vandestopper: An Anti-Vandalism Detection System for Fire Extinguisher - Nor Faezah Adan,; Muhammad Idzhan Marjohan,; Muhammad Azim Sanep,; Muhammad Yudiazwie Muhammad Zaidi, (Multidisciplinary Applied Research and Innovation, 2023)
Loss and damage of fire extinguishers as a result of vandalism among students, especially in schools. Research has been conducted to assist in dealing with vandalism on school fire extinguishers.The method used in this research is to detect the location of the appliance, get an image of the nearby area and provide notifications to the user in the smartphone application. There are two separate systems for capture images of vandalism and locate fire extinguishers. System 1 uses the NodeMCU ESP8266 and GPS Module while the system 2 uses the ESP32- CAM and IR sensors. Both systems are connected to blynk on the user's smartphonebut it requires Wifi to send information to the blynk. What can be concluded is that blynk will notify the user that the fire extinguisher is removed along with the vandalism image and location of the extinguisher as soon as the IR sensor detects the fire extinguisher being removed. The suggestion to solve this problem is that Blynk app needs to improve its efficiency and functionality so that it can show clear location and picture as well as get notification quickly.